AN OVERVIEW OF NANOPARTICLES: METHODS OF OBTAINING, APPLICATIONS AND CHARACTERISTICS (Nonconventional Technologies Review, 2025)
Lately, the term of “Nanotechnology” becomes very popular. This combines different representations and interpretations of action methods on materials. It means, before proceeding to characterization, methods of obtaining and applications, it is necessary to clarify about which dimensions will be further discussed. Is clear, that the term of “Nanotechnology” becomes obtained from two words: “nano” that means looking into a scale of billionth part (10-9) and “technology” – the application of knowledge in practice. So hard to imagine these dimensions and to clarify a little, it’s important to mention that the thinnest atom of Hydrogen has a diameter of a 10-10 m and especially the DNA spiral has the diameter of 1 nm. So, nanotechnology can be defined as a set of technics and methods, based on manipulation with atoms and molecules in a scale from 1 to 100 nm. The usage of special characteristics of materials in a scale of some couples of nanometers discovers new possibilities of development of process technologies in a strong link with electronics, material study, chemistry, medicine, mechanics and a lot of science branches. Obtaining new materials and development of new methods conduits to a technic-scientific revolution in information technology, obtaining new construction materials, producing medical preparations, construction of super exact devices etc. The overview in the following paper is designed to facilitate informed people and a reference for researchers and professionals regarding the know-how transfer, multidisciplinary collaboration and further development of methods of obtaining, applications and characterization on nanomaterials.
Keywords: nanotechnology; nanoparticle; nanomaterial; synthesis; discharge; explosion